Manajemen Bencana Non Alam Covid-19 Dilihat Dari Kepemimpinan Quadruple Helix Di Kota Mataram - Inka Nusamuda Pratama; Ayatullah Hadi; Ilham Zitri (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2021)
The study in this study wanted to know about the leadership role of the Quadruple Helix in Covid-19 non-natural Disaster Management in Mataram City, West Nusa Tenggara Province. Quadruple Helix leadership is a form of leader capacity who is an actor who has successfully collaborated in disaster response. The Quadruple Helix leadership model in the Unitary State of Regional Autonomy can be implemented with the Government acting as a regulator and implementing socialization, then Academics are tasked with making research and issuing their latest innovation products, while Business or Private plays a role as fund support, and the Community participates in supporting policies. The form of active collaboration between the Government, the private sector, universities and the community is the basis of the Covid-19 non-natural disaster management system as an effort to handle and mitigate. The method used in this study is qualitative research with interview data collection techniques to related stakeholders. The results in this study were the management of non-natural Covid-19 disasters in Mataram City using the Quadruple Helix model running well. The cooperation of the four (Government, Academics, Business/Private and Community) was able to suppress the spread of Covid-19 in Mataram City. Collaboration from all existing Helix is ​​needed to continue to encourage the birth of innovations in the field of knowledge, formulation of ideal and targeted policies, support for assistance and donations in the form of logistics and medical devices, and mutual understanding from the community that is able to have a positive impact in suppressing the spread of Covid -19 in Mataram City.